AI-Powered Teaching: Literature Review of ChatGPT’s Impact on University Educators - Holubnycha, Liudmyla; Kuznetsova, Olena; Shchokina, Tetiana; Soroka, Natalia; Demchenko, Dina; Koshechkina, Tetyana; Kovalenko, Oksana (International Journal of Interactive Mobile Technologies (iJIM), 2025)
The conversational artificial intelligence (AI) model ChatGPT has drawn significant interest from educators, as it opens up opportunities for innovations and provides substantial potential for use by university instructors. Since there is a lack of certainty about the effective application of ChatGPT in university teaching, the research reviews the available scientific studies to address these questions. The systematically analysed data cover two years (30.11.2022–30.11.2024). Based on the tasks set, the research identifies the spheres of university educators’ activities in which ChatGPT offers educationally valuable assistance. The ChatGPT-assisted teaching activities are examined and analysed with special attention to the benefits and concerns that the application of ChatGPT may bring to university teaching. ChatGPT’s integration into mobile-supported learning settings, highlighting its role in enabling ubiquitous learning, real-time feedback, and adaptive teaching support, is scrutinised. The recommendations for coping with the perceived negative aspects of ChatGPT in university educators’ teaching are revealed and highlighted. The distinct role of ChatGPT as a supportive means in university teaching is supported.